Systematic Literature Review of Curriculum Management in Improving Educational Quality in Indonesia - Michael Harry Widyarto Setiawan; Lia Yuliana (South Sulawesi Education Development (SSED), 2026)
Curriculum reform has been a widely discussed topic during every change of government, from its name to its implementation, and has generated various reactions. This study aims to examine curriculum management to improve the quality of education in Indonesia, from elementary school through university, rather than at a single level. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. The data sources comprised 41 relevant scientific articles on curriculum management to improve the quality of education in Indonesia for the 2020-2024 period, collected via Google Scholar, Crossref, Scopus, and PubMed using the Publish or Perish tool. The results of the study indicate that curriculum management follows the classic educational management model, which involves four main components: Planning, Organizing, Implementation, and Evaluation (using a model such as CIPP) at all levels of education, resulting in 1) Improved Graduate Quality: Both in terms of academics and character, including spirituality in faith-based schools. 2) More Relevant Learning: With a project approach and student-based learning. 3) Readiness for Change: Schools are better prepared to face the demands of the times, the pandemic, and technology. Challenges include balancing the national and local/religious curricula, and systemic and technical constraints in implementing curriculum management, which is unique to Indonesia. This research can provide a theoretical basis for further curriculum improvements to produce a high-performing generation across all levels of education.